2022
DOI: 10.1038/s41598-022-25680-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Rayleigh wave propagation in thermoelastic media in dual-phase-lag

Abstract: A model of generalized thermoelasticity within dual-phase-lag is used to investigate nonlinear Rayleigh wave propagation in a half-space of a transversely isotropic elastic material. It is assumed that the coefficient of heat conduction is temperature-dependent, a fact that plays an important role in the coupling behaviour analysis of thermoelastic and piezo-thermoelastic solids. Taking such a dependence into account becomes a necessity at higher temperatures and in nano-structures, when the material propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Figures 4 and 5 are devoted to the comparison of solutions at the first and the second orders of approximation respectively between the cases of a half-space with/without slab. The results for the half-space without slab were recently published by the same authors 20 . According to these figures, we concluded that the presence of the bonded slab yields faster attenuation of the solution with depth.…”
Section: Numerical Results and Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Figures 4 and 5 are devoted to the comparison of solutions at the first and the second orders of approximation respectively between the cases of a half-space with/without slab. The results for the half-space without slab were recently published by the same authors 20 . According to these figures, we concluded that the presence of the bonded slab yields faster attenuation of the solution with depth.…”
Section: Numerical Results and Discussionmentioning
confidence: 97%
“…Body forces and heat sources are disregarded. The dimensionless equations of plane thermoelasticity for a transversely isotropic material within the theory of extended thermodynamics to be considered are expressed in 19 , 20 . They involve the equations of motion, the equation of energy, the evolution laws for the heat flux components and the generalized Hooke’s laws differentiated w.r.t.…”
Section: Basic Equationsmentioning
confidence: 99%
See 3 more Smart Citations